Analysis of interelectrode short-circuit current in industrial copper electrorefining cells. (November 2020) - Zeng, Qingyu; Li, Chun; Meng, Yi; Tie, Jun; Zhao, Rentao; Zhang, Zhifang
Highlights: Using optical fiber current sensor to monitor the process of electrode short-circuit. The characteristics of complete cathode current curve in the short-circuit process. A method to diagnose short-circuit quickly by slope & standard deviation of current. Abstract: In the process of copper electrorefining, detecting and treating the interelectrode short-circuit faults is one of the main tasks in the workshop. In this paper, the cathode current in industrial copper electrorefining cells was measured by an optical fiber current sensor, and the current curves caused by interelectrode short-circuit have been obtained. The relationship between the characteristics of cathode current and the mechanism of interelectrode short-circuit is discussed. A rapid diagnostic method of short-circuit faults by monitoring the change of cathode current slope and standard deviation is proposed. The applicable scope of the method is also given.